A new method for pull out test of reinforcing bars in plain and fibre reinforced concrete. (1st June 2018) - Chu, S.H.; Kwan, A.K.H.
Highlights: A new pull-out test with rubber and PTFE at contact interface is developed. Pull-out tests of steel bars in plain and fibre-reinforced concrete conducted. The new test method yields lower and less variable bond properties results. It would provide more accurate bond properties for analysis and design. Abstract: The bond of reinforcing bars in concrete is crucial in anchorage of reinforcing bars and crack control of reinforced concrete. It is generally measured by pull out test of a reinforcing bar embedded in a concrete block. However, the different test methods yield different test results. In this research, finite element analysis was carried out to reveal the variations in stress distribution inside the concrete block due to uneven contact pressure and friction at the concrete block-steel platen interface of the test setup. To minimize the test errors due to such uneven contact pressure and friction, the test setup was redesigned by inserting a rubber pad and a PTFE film at the interface. Using the redesigned setup, pull out tests of reinforcing bars in plain and fibre reinforced concrete were conducted and the results compared to those obtained without rubber pad or PTFE film installed. It was found that the new test would yield lower and less variable bond strength and stiffness results. This improved test method would provide more accurate bond properties for structural analysis and design.